2022
DOI: 10.3390/ma16010162
|View full text |Cite
|
Sign up to set email alerts
|

Some Slippage Issues in High-Pressure Torsion Using Cu and Ti Samples as an Example

Abstract: The effect of slippage during High Pressure Torsion (HPT) of technically pure Ti and pure Cu samples was investigated. The “joint torsion of the disk halves” method was used to evaluate the effect of slippage. It was shown that slippage starts already at the early stages of HPT. With a further increase in the number of revolutions n, the slippage effect increases, and no torsional deformation occurs after n = 5. The slippage effect is explained by analyzing the surface friction forces between the sample and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Thus, after the preliminary HPT with n = 5, complete slippage was obs on the Ti specimen. As shown above (Figure 4a), the slippage effect was not so significant in the i stages (n = ¼) of the HPT of Cu [28]. However, we decided to investigate how the slip on Cu changes as the number of HPT revolutions increases.…”
Section: Overview Of Slippage In Hptmentioning
confidence: 82%
See 4 more Smart Citations
“…Thus, after the preliminary HPT with n = 5, complete slippage was obs on the Ti specimen. As shown above (Figure 4a), the slippage effect was not so significant in the i stages (n = ¼) of the HPT of Cu [28]. However, we decided to investigate how the slip on Cu changes as the number of HPT revolutions increases.…”
Section: Overview Of Slippage In Hptmentioning
confidence: 82%
“…The authors of the present paper have used the "joint HPT of two halves" method for the past 4 years to evaluate slippage on a number of metallic materials, see, e.g., [24][25][26][27]. It was shown that slippage on such a relatively mild material as copper was not so significant in the early stages of HPT [25,28]. However, during the HPT of such materials as mild steel (Fe-0.1% C), the Zr-1%Nb alloy, CP Ti, the β-Ti alloy, Ti-18Zr-15Nb, and the austenitic steel 316 (Fe-0.03C-17Cr-0.41Si-1.72Mn-0.01P-0.03S-12.9Ni-2.36Mo, wt.%) the slippage was revealed as follows [26][27][28]: samples of these materials received a certain degree of shear strain at the initial HPT stages, but significant slippage was observed already at the initial stages of HPT.…”
Section: Overview Of Slippage In Hptmentioning
confidence: 95%
See 3 more Smart Citations